Prevalence and Antimicrobial Resistance Pattern of Blood Isolates in Patients of Septicemia in ICU: Single Centre Observation - Ahsan, ASM Areef; Fatema, Kaniz; Barai, Lovely; Faruq, Mohammad Omar; Ahmed, Fatema; Saha, Debasish Kumar; Saha, Madhurima; Nazneen, Suraiya; Hamid, Tarikul; Zabeen, Nazia (Bangladesh Critical Care Journal, 2016)
Background: Septicaemia in critically ill patients is a life threatening condition and requires rapid antimicrobial treatment. Infections caused by drug-resistant organisms are more likely to increase risk of death in these patients. The present study was aimed to study the profile of organisms causing septicaemia and their antibiotic resistance pattern in an intensive care unit (ICU) of a teaching hospital in Bangladesh. Materials and Methods: This cross-sectional study was done in a 21-beded adult ICU of Dhaka city from November 2015 to April 2016. Results: A total of 362 patients were diagnosed clinically as septicaemia during the study period of six month. 696 blood samples were analyzed and 92 blood samples yielded growth of 94 organisms, which included 89 bacteria and 5 fungal isolates. Mean age of the patients whose blood samples showed growth of organisms was 65.1 ± 9.1 years, with female preponderance (56.7%). High prevalence of diabetes, hypertension and chronic kidney disease was found in these patients. The major organisms isolated were Acinetobacter (29.7%), Pseudomonas (26.5%), Klebsiella (18.08%), Eschericia coli (11.7%) and Candida (5.3%). All the isolates were resistant (>50%) to 3rd generation cephalosporins. Acinetobacter was highly resistant (>75%) to most of the antibiotics except colistin. Isolated Pseudomonas was also resistant to aminoglycosides (>90%) and imipenem (>65%). Klebsiella was resistant to aminoglycosides and imipenem, but Eschericia coli was sensitive to these antibiotics. Among the Enterobacteriaceae, 81.8% Eschericia coli and 11.7% Klebsiella had extended spectrum ?-lactamase activity. Frequency of gram positive organisms (6.38%) was significantly low in this study (p<0.05). Conclusion: This study provides information on antibiotic resistance of blood isolates found in ICU patients with septicaemia. It will guide the intensivists to formulate the initial empiric antibiotic therapy for the critically ill patients of ICU. Bangladesh Crit Care J September 2016; 4 (2): 100-104